Click‐Chemistry‐Mediated Rapid Microbubble Capture for Acute Thrombus Ultrasound Molecular Imaging. (7th June 2017) - Wang, Tuantuan; Yuan, Chuxiao; Dai, Bingyang; Liu, Yang; Li, Mingxi; Feng, Zhenqiang; Jiang, Qing; Xu, Zhihong; Zhao, Ningwei; Gu, Ning; Yang, Fang
Abstract: Bioorthogonal coupling chemistry has been studied as a potentially advantageous approach for molecular imaging because it offers rapid, efficient, and strong binding, which might also benefit stability, production, and chemical conjugation. The inverse‐electron‐demand Diels–Alder reaction between a 1, 2, 4, 5‐tetrazine and trans ‐cyclooctene (TCO) is an example of a highly selective and rapid bioorthogonal coupling reaction that has been used successfully to prepare targeted molecular imaging probes. Here we report a fast, reliable, and highly sensitive approach, based on a two‐step pretargeting bioorthogonal approach, to achieving activated‐platelet‐specific CD62p‐targeted thrombus ultrasound molecular imaging. Tetrazine‐modified microbubbles (tetra‐MBs) could be uniquely and rapidly captured by subsequent click chemistry of thrombus tagged with a trans ‐cyclooctene‐pretreated CD62p antibody. Moreover, such tetra‐MBs showed great long‐term stability under physiological conditions, thus offering the ability to monitor thrombus changes in real time. We demonstrated for the first time that a bioorthogonal targeting molecular ultrasound imaging strategy based on tetra‐MBs could be a simple but powerful tool for rapid diagnosis of acute thrombosis. Abstract : Real‐time thrombosis imaging : Click coupling between tetrazine‐modified microbubbles and CD62p tagged with trans ‐cyclooctene allows a fast, reliable, and highly sensitive ultrasound molecular imaging approach to capture activated‐platelet‐specific CD62p‐targeted thrombus. This method could be a simple but powerful tool for rapid and real‐time diagnosis of acute thrombosis.